Epidemiological Study on Canine Babesiosis in Jaipur, Rajasthan, India - Choudhary, Akanksha; Singh Meena, Dharm; Singh, Rashmi; Bargujar, Jitendra; Mandawat , Saksham (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted on dogs suspected for babesiosis (n=100), in Jaipur (Rajasthan, India) presented with the history of inappetence to anorexia, pyrexia, tick infestation, lethargy and signs of anaemia. Out of 100 dogs, 24 (24%) were found positive for Babesia spp., which were confirmed by polymerase chain reaction. The highest incidence of canine babesiosis was seen in the age group of 1-5 years (29.16%), sex-wise in male dogs (25.92%) and breed-wise in Labrador Retrievers (34.78%). Clinical observations in 24 babesiosis positive dogs revealed anorexia in 23 dogs, fever/pyrexia and tick infestation in 21 dogs, depression and lethargy in 19 dogs, lymphadenopathy in 15 dogs and pale mucous membrane in 9 dogs.
Keywords: Babesiosis; Canine; Epidemiology; Jaipur